Adipogenic Differentiation of Mesenchymal Stem Cells Alters Their Immunomodulatory Properties in a Tissue‐Specific Manner. (24th April 2017) - Munir, Hafsa; Ward, Lewis S. C.; Sheriff, Lozan; Kemble, Samuel; Nayar, Saba; Barone, Francesca; Nash, Gerard B.; McGettrick, Helen M.
Abstract: Chronic inflammation is associated with formation of ectopic fat deposits that might represent damage‐induced aberrant mesenchymal stem cell (MSC) differentiation. Such deposits are associated with increased levels of inflammatory infiltrate and poor prognosis. Here we tested the hypothesis that differentiation from MSC to adipocytes in inflamed tissue might contribute to chronicity through loss of immunomodulatory function. We assessed the effects of adipogenic differentiation of MSC isolated from bone marrow or adipose tissue on their capacity to regulate neutrophil recruitment by endothelial cells and compared the differentiated cells to primary adipocytes from adipose tissue. Bone marrow derived MSC were immunosuppressive, inhibiting neutrophil recruitment to TNFα‐treated endothelial cells (EC), but MSC‐derived adipocytes were no longer able to suppress neutrophil adhesion. Changes in IL‐6 and TGFβ1 signalling appeared critical for the loss of the immunosuppressive phenotype. In contrast, native stromal cells, adipocytes derived from them, and mature adipocytes from adipose tissue were all immunoprotective. Thus disruption of normal tissue stroma homeostasis, as occurs in chronic inflammatory diseases, might drive "abnormal" adipogenesis which adversely influences the behavior of MSC and contributes to pathogenic recruitment of leukocytes. Interestingly, stromal cells programmed in native fat tissue retain an immunoprotective phenotype. Stem Cells 2017;35:1636–1646 Abstract : In coculture with endothelial cells (EC), adipose‐derived stromal cells (ADSC) and adipocytes differentiated from them are immuno‐protective, limiting both neutrophil and lymphocyte recruitment during inflammation. In contrast, while MSC isolated from non‐adipose tissue are immunosuppressive, they lose this capability following ectopic adipogenesis, so that inflammation may occur unchecked. Thus adipocytes may exist in at least two functional states: (A) immunosuppressive as found in healthy adipose tissue and (B) stimulatory in sites of ectopic (chronic inflammation) fat deposition. Secreted IL‐6 appears able to inhibit or promote leukocyte recruitment depending on other factors released in the different milieu.